Improvement of Learning Results on Islamic History Lesson of KMI Class 2E by Through Strategy Questions Students Have Question Students Have at Darussalam Gontor Modern Islamic Boarding School for Girls Campus Three on Academic Year 1441-1442 H. - Nurul Azizah; Cynthia Maristanty (Prodi Pendidikan Agama Islam, Fakultas Tarbiyah, Universitas Darussalam Gontor, 2021)
AbstrackThis research is motivated by the low learning activities of students who have an impact on the results of low students learning and have not met the standards. According to research from the values that have been achieved, especially in the subjects of Islamic Date, more than 80% of all students have not reached the standard value (KKM) of 4.8 that has been determined by the Central Gontor. The students could not answer questions from teachers, namely from 38 students in this class only 3 people (7.89%) who achieved the standard score while 35 others (92.10%) has not reached the value (KKM). Researchers use The Question Students Have Strategy because this strategy is interesting, eliminates boredom, is more active, so that the classroom atmosphere is more lively, children can train themselves to ask and make questions using Arabic, so it is easy to draw conclusions based on their own passions. Researchers try to use Learning Strategies to support learning in the classroom by using The Question Students Have Strategy in Islamic Date lessons class 2E KMI because researchers want to improve the activeness and learning outcomes of students by using these strategies. So the value that must be achieved by learners is 75% in each cycle.This study uses Class Action Research (PTK) method, in Islamic Date subjects. Class Action Research (PTK) is conducted 2 cycles, each cycle consists of four stages, planning, implementation, observation, and reflection. At the planning stage teachers prepare RPP, student worksheets, instruments used in the learning evaluation cycle and tools. At the stage of implementation of mambagi teachers in groups, using learning strategies and conducting observations or observations. In the observation stage, researchers observed the situation of teaching and learning activities, students' activeness, and students' ability to perform learning strategies. At the reflection stage, researchers conducted data analysis by categorizing and collecting data collecting and using tests to obtain learning results in Islamic Date lessons santriwati class 2E KMI using Question Students Have Strategy.The results of this study showed that by applying the Question Strategy Students Have can: 1) improve the learning outcomes of students and 2) the activeness of learning santriwati. In the first cycle of activeness of students reached 74.34%, then increased in the second cycle of 77.13%. The learning outcomes of students in the first cycle reached 34.21%, then increased in the second cycle of 92.10%. It can be concluded that the average value in the first cycle is 3.71 and the average value in the second cycle is 5.03.From the study, researchers advised all teachers who master islamic date subject matter to use The Question Students Have Strategy during the learning process. Because this Strategy is appropriate and effective for use in islamic date lesson materials class 2 KMI.